ONLINE LEARNING DURING THE PANDEMIC AT GEOGRAPHY TEACHERS AT SMAN 15 BANDAR LAMPUNG IN 2021 - Indah Wulandari; Pargito Pargito; Listumbinang Halengkara (Journal Learning Geography, 2022)
The purpose of this study is to find out online learning during the geography teacher at SMA Negeri 15 Bandar Lampung. The method used in this research is qualitative study with case study method. The subject in this study is a geography teachers at SMA Negeri 15 Bandar Lampung with 2 respondents while the object of this study is online learning. Data collection techniques used the main techniques that interviews and support techniques that are observation and literature study. The data analysis technique in this study uses the data analysis technique of the Milles and Huberman model. The results showed that the application of online learning during the pandemic included teachers understanding of learning, it can be seen that teachers have used the principles of online learning, the use of learning media is still monotonous, and the use of the teacher’s method of passive learning , the facilities and infrastructure provided bye the school can support teacher learning, the obstacles experienced by teachers in online learning are the constraints of providing material, less learning time, and lak of interaction between students and teachers.